El espacio como magnitud econométrica: valoración del espacio - Gálvez Laguarta, Eduardo María (1959)
In first part of the work, it is intended to leave the difference between value and space value, well set up. The latter is analyzed as a magnitude, it is classified and specified a space value, its dimension is considered and so are the concepts of cardinal and ordinal space, to end with the determination of the concept of value of the space, the price, and the difference between concrete and concreting space